PLANEJAMENTO ESTRATÉGICO NA INDÚSTRIA DA CONSTRUÇÃO CIVIL: ÁREAS, TEMAS, TÉCNICAS E MÉTODOS - Gomes, Maria Micheline Barreto; Cavalcante Filho, João Umberto de Paula; Barros Neto, José de Paula (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Strategic planning is relevant to the performance and development of the construction industry. Due a highly competitive market, it is necessary for companies to develop and implement adequate strategic planning in their businesses. This paper aims to answer the following research question: what are the main areas, themes, techniques and methods addressed in the construction sector with the theme strategic planning? The method was seeking the interaction of the terms in pairs, in articles published in the period from 2013 to 2017 that relate strategic planning and civil construction. This article contributes to the understanding of the areas, themes, techniques and methods of the use of strategic planning in civil construction according as literature review that presents the correlation between the subjects.